46 Inpatient admissions for lower gastrointestinal bleeding in the belfast trust. (5th April 2017) - Clarke, E; Cooper, P; Turner, GB
Abstract : Background: Traditionally, lower GI bleeding (LGIB) is admitted surgically but the recent NCEPOD report has recommended an integrated pathway for all gastrointestinal bleeds. Aim: To retrospectively assess how LGIB is managed within the Trust. Method: Inpatient discharge data were gathered over a 12 month period (March 2015-March 2016). Cases included were those with LGIB as the primary reason for admission. Factors including length of stay, inpatient and/or outpatient endoscopic and radiological investigations. 30 day mortality rate was assessed. Results: 350 patients were identified, 174 were excluded (UGIB or not primary reason for admission). 176 patients were included, age range 17–100 (median 66). Median length of stay=3.19 days (range 0–27). Total bed days 562. 30 day mortality=3.9% (n=7, 2 secondary to PR bleeding and 5 due to co-morbidities). n=86 (48.9%) patients had inpatient investigations. See Figure 1 . 50 patients had only inpatient endoscopic procedures, 15 had both endoscopic and radiological investigations and 15 had only radiological investigations. Others included EUA and haemorrhoidectomy. n=46 (26.1%) had only outpatient investigations. Total bed days=83. n=44 (25%) had no investigations. Reasons included known pathology, recent endoscopy or CT imaging, recent intervention (surgical or endoscopic) or not fit for investigation. Most common diagnoses were diverticular bleed n=59, haemorrhoids n=12, malignancy n=10. Conclusions: Less than half had inpatient investigations suggesting that many admissions could have been avoided. The current results show a low mortality rate consistent with other published data. A pathway for the management of stable LGIB bleeding could be developed to minimise unnecessary admissions and streamline access to intervention where needed.